Gregg syndrome: With blueberry muffin rash and congenital cataract - Shyamkumar Makadia; Hiral Shah; Bharti Patel; Neela Bhuptani (Wolters Kluwer Medknow Publications, 2016)
Rubella, though a mild, vaccine-preventable disease, can manifest with severe teratogenic effects in the fetus due to primary maternal rubella infection. A case of a full-term neonate with blueberry muffin lesions and classical as well as rare systemic features of Gregg syndrome is reported.